2017
DOI: 10.3847/1538-4357/aa8ee7
|View full text |Cite
|
Sign up to set email alerts
|

Branching Ratios in Vacuum Ultraviolet Photodissociation of CO and N2: Implications for Oxygen and Nitrogen Isotopic Compositions of the Solar Nebula

Abstract: . After weighting the absorption cross-sections for individual photodissociation bands, and taking into account the mutual shielding by H 2 , the CO/N 2 ratio, and the partition of O and N among gas:ice:dust phases in the solar nebula, we show that the trapping of N( 2 D) via hydrogenation is favored over that of O( 1 D). This provides a possible explanation of the Genesis results and supports the self-shielding model as the primary mechanism for generating isotopic anomalies of O and N in the early solar nebu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…By using the measured branching ratios and the photoabsorption cross sections of 12 C 16 O and 14 N 2 reported in the literature, Shi et al carefully modeled the possible fractionation processes of O and N isotopes in the framework of self-shielding models by considering the different chemical reactivity between the excited O( 1 D) [N( 2 D)] and the ground O( 3 P) [N( 4 S)] produced by VUV photodissociation of CO [N2]. The modeling results qualitatively support the observations by the Genesis mission 24 . Besides O and N, Lyons et al have recently showed that the heavy C isotope ( 13 C) is also depleted in the Sun compared with that in the Earth and other planetary objects 25 .…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…By using the measured branching ratios and the photoabsorption cross sections of 12 C 16 O and 14 N 2 reported in the literature, Shi et al carefully modeled the possible fractionation processes of O and N isotopes in the framework of self-shielding models by considering the different chemical reactivity between the excited O( 1 D) [N( 2 D)] and the ground O( 3 P) [N( 4 S)] produced by VUV photodissociation of CO [N2]. The modeling results qualitatively support the observations by the Genesis mission 24 . Besides O and N, Lyons et al have recently showed that the heavy C isotope ( 13 C) is also depleted in the Sun compared with that in the Earth and other planetary objects 25 .…”
Section: Introductionmentioning
confidence: 58%
“…Even though not mentioned in the above two examples, they actually both assumed that all CO isotopologues produce the same amount of O and C atoms in the excited states, the validity of which has not been experimentally proved yet 24,25 . In the present work, we measure the photodissociation branching ratios of 13 C 16 O in the Rydberg 4p(2), 5p(0) and 5s(0) complex region and find that the percentages of producing C( 1 D) and O( 1 D) for 13 C 16 O can be dramatically different from that for 12 C 16 O in the same absorption band, revealing very strong isotope effect.…”
Section: Introductionmentioning
confidence: 98%
“…This global comparison of the branching ratios into the spin-forbidden channel between different CO isotopologs should be extremely useful in mapping out the detailed Rydberg-Rydberg, Rydberg-valence interactions, which are important for understanding the predissociation dynamics of CO, and should benchmark any future theoretical calculations. Whether or not the strong isotope effect of the photodissociation branching ratio as observed here can affect the C isotope fractionation process that happened in the Solar System is still awaiting quantitative photochemical modeling, which should include the CO self-shielding effect and also the shielding effect from the H/H 2 absorption (Shi et al 2017;Lyons et al 2018).…”
Section: Upper Statementioning
confidence: 96%
“…Whole spectroscopic studies have been devoted to characterizing the molecular parameters of all CO isotopologs so that the astronomical observations can be better interpreted and to further improve the photochemical modeling (Eidelsberg & Rostas 1990;Eidelsberg et al 1991Eidelsberg et al , 1992Eidelsberg et al , 2004Eidelsberg et al , 2006Eidelsberg et al , 2012Eidelsberg et al , 2014Eidelsberg et al , 2017Eikema et al 1994;Ubachs et al 1994;Stark et al 2014;Lemaire et al 2018), but very few studies have discussed the subsequent "trapping reactions" following the VUV photodestruction process of CO (Clayton 2011;Shi et al 2017;Lyons et al 2018). Recently, Lyons et al (2018) reanalyzed the ATMOS FTS data and found that the heavy C isotope ( 13 C) is also depleted in the Sun compared with that in the Earth and other planetary objects.…”
Section: Introductionmentioning
confidence: 99%
“…While these spectroscopic parameters are important for understanding the predissociation dynamics of CO and have key applications in astrochemistry, no information about the quantum state distributions of the C and O atom photofragments can be obtained from the spectroscopic measurements. This information is important for chemical modeling of the interstellar medium, since electronic excited C( 1 D) and O( 1 D) atoms have much higher reactivities towards H 2 than the ground C( 3 P) and O( 3 P) atoms, thus might play much more important roles in the low temperature interstellar medium [36,37]. Following the absorption of a single VUV photon, CO can have the following three dissociation channels:…”
Section: B Comentioning
confidence: 99%